Working for a good retirement - Barbara A. Butrica; Karen E. Smith; C. Eugene Steuerle (Levy Economics Institute of Bard College, 2006)
The choice of retirement age is the most important portfolio choice most workers will make. Drawing on the Urban Institute's Dynamic Simulation of Income model (DYNASIM3), this report examines how delaying retirement for nondisabled workers would affect individual retiree benefits, the solvency of the Social Security trust fund, and general revenues. The results suggest that delaying retirement by itself does not generate enough additional revenue to make Social Security solvent by 2045. Benefit cuts or supplementary funding sources will be necessary to achieve solvency. However, the size of the benefit cuts or tax increases could be minimized if individuals worked longer. This additional work also substantially increases worker's retirement well-being. Lower-income workers, to the extent they can work longer, have the most to gain from their additional labor. Policy changes that encourage work at older ages will substantially improve both economic and personal well-being in the future.
Keywords: J26; H6; I3; 330; Retirement; Social Security; taxes; federal deficit; retirement well-being